EUropean prospective cohort study on Enterobacteriaceae showing REsistance to CArbapenems (EURECA): a protocol of a European multicentre observational study. Issue 4 (3rd April 2017) - Gutiérrez-Gutiérrez, Belén; Sojo-Dorado, Jesús; Bravo-Ferrer, José; Cuperus, Nienke; de Kraker, Marlieke; Kostyanev, Tomislav; Raka, Lul; Daikos, George; Feifel, Jan; Folgori, Laura; Pascual, Alvaro; Goossens, Herman; et al.
Abstract : Introduction: The rapid worldwide spread of carbapenem-resistant Enterobacteriaceae (CRE) constitutes a major challenge. The aim of the EUropean prospective cohort study on Enterobacteriaceae showing REsistance to CArbapenems (EURECA), which is part of the Innovative Medicines Initiative Joint Undertaking (IMI JU) funded COMBACTE-CARE project, is to investigate risk factors for and outcome determinants of CRE infections to inform randomised clinical trial designs and to provide a historical cohort that could eventually be used for future comparisons with new drugs targeting CRE. Methods: A multicentre (50 sites), multinational (11 European countries), analytical observational project was designed, comprising 3 studies. The aims of study 1 (a prospective cohort study) include characterising the features, clinical management and outcomes of hospitalised patients with intra-abdominal infection, pneumonia, complicated urinary tract infections and bloodstream infections caused by CRE (202 patients in each group). The main outcomes will be 30-day all-cause mortality and clinical response. Study 2 (a nested case–control study) will identify the risk factors for target infections caused by CRE; 248 selected patients from study 1 will be matched with patients with carbapenem-susceptible Enterobacteriaceae (1:1) and with hospitalised patients (1:3) and will provide a historical cohort of patients with CRE infections. Study 3 (a matched cohort study) will follow patients in study 2 in order to assess mortality, length of stay and hospital costs associated with CRE. All patients will be followed for 30 days. Different, up-to-date statistical methods will be applied to come to unbiased estimates for all 3 studies. Ethics and dissemination: Before-study sites will be initiated, approval will be sought from appropriate regulatory agencies and local Ethics Committees of Research or Institutional Review Boards (IRBs) to conduct the study in accordance with regulatory requirements. This is an observational study and therefore no intervention in the diagnosis, management or treatment of the patients will be required on behalf of the investigation. Any formal presentation or publication of data collected from this study will be considered as a joint publication by the participating physician(s) and will follow the recommendations of the International Committee of Medical Journal Editors (ICMJE) for authorship. Trial registration number: NCT02709408.